Potret Akuntansi Pohongi Berbasis Nilai Budaya Islam Gorontalo: Studi Etnometodologi Islam - Mohamad Anwar Thalib (Kunuz: Journal of Islamic Banking and Finance, 2022)
This study aims to photograph the practice of capital accounting based on the local wisdom values of the Gorontalo community. This study uses an Islamic ethnomethodology approach which is under the Islamic paradigm. There are five data analysis stages: charity, knowledge, faith, revelation information, and good deeds. The study results found that patience and belief that the Creator has arranged sustenance are non-material assets owned by the coachmen. This capital makes them stick with the profession even though the number of users is getting smaller. In the culture of the people of Gorontalo, patience and belief in God are often expressed through lumadu tanggalo duhelo”, which means full of patience in dealing with problems. This research contributes to presenting the concept of capital accounting based on Islamic cultural values in the Gorontalo area. This study also confirms that accounting is a science that requires cultural values and faith in God